2015
DOI: 10.1063/1.4933100
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling-percolation behavior of polydisperse prolate and oblate ellipsoids

Abstract: We report Monte Carlo simulations of systems of polydisperse prolate and oblate ellipsoids using the critical path based tunneling-percolation model. For polydisperse prolate ellipsoids, the critical percolation volume fraction ϕc is shown to have a quasi-universal dependence on weight-averaged aspect ratio. For polydisperse oblate ellipsoids, ϕc is shown to have a quasi-universal dependence on the apparent aspect ratio, which is a function of up to fourth moment of the size distribution, as given by the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…It treats two-body connectedness probabilities analogously to liquid state correlation functions and has been widely applied in the context of spherical and nonspherical particles and mixtures thereof [2,6,9,32,33]. In particular for slender rod-like particles, the agreement with results from Monte Carlo simulations is excellent [20,21,25,34,35].…”
Section: Connectedness Percolation Theorymentioning
confidence: 99%
“…It treats two-body connectedness probabilities analogously to liquid state correlation functions and has been widely applied in the context of spherical and nonspherical particles and mixtures thereof [2,6,9,32,33]. In particular for slender rod-like particles, the agreement with results from Monte Carlo simulations is excellent [20,21,25,34,35].…”
Section: Connectedness Percolation Theorymentioning
confidence: 99%
“…Next to the connectivity range, there are many factors that influence the formation of transient networks in nanoparticle dispersions. A vast body of literature has shown that the particle anisometry, [15][16][17][18][19] size polydispersity, [13][14][15][19][20][21][22][23][24][25][26] the presence of nonconducting particles, [15] inter-particle interactions [27][28][29] and external fields [18,30] can have tremendous effects on the percolation threshold, while the influences of flexibility and the precise particle shape seem to be rather subtle. [27,31,32] In this article we focus on the fact that many types of conductive nanoparticle, like carbon nanotubes or graphene, have a strongly anisotropic shape, which strongly affects their interactions and the way they react to external orienting fields.…”
Section: Introductionmentioning
confidence: 99%
“…When applied to dispersions of rods with inter-particle tunnelling, these results amount to predict that the critical tunnelling distance δ c depends upon the rod length distribution only through L w for a given volume fraction of the nanotubes 11,13,26 . The resulting bulk conductivity σ is thus expected to display a similar quasi-universal behaviour as a function of L w , implying that knowledge of the scaled variance of L, 〈 〉 〈 〉 − L L / 1 2 2 , is necessary in order to control σ.…”
mentioning
confidence: 96%